Fuzzy Clustering Based Blind Adaptive OFDM System - Twayana, Krishna Sundar; Joshi, Shashidhar Ram (Journal of Advanced College of Engineering and Management, 2016)
This paper present blind adaptive modulation for OFDM system. Automatic recognition of the modulation level of detected signal and blind estimation of SNR is a major task of an intelligent receiver presented here. In this paper, modulation classification is performed by fuzzy c-means clustering followed by new approach of modulation classification, fuzzy template matching considering the constellation of the received signal. In addition, SNR estimation and modulation order for the next transmission is carry out by Fuzzy Logic Interface based upon heuristics. The simulation that has been conducted shows high capability of recognition of modulation level, almost perfect estimation of SNR and adaptive with considerable BER in an Additive White Gaussian Noise channel. The performance of proposed system is simulated in computer simulation tool, MATLAB 7.0. Journal of Advanced College of Engineering and Management, Vol.1, 2015, pp. 51-58